The diversity of puring (Codiaeum variegatum (Linn.) Blume) in Yogyakarta - MUZAYYINAH MUZAYYINAH (Society for Indonesian Biodiversity, 2003)
Puring (Codiaeum variegatum (Linn.) Blume) which is native to Ambon has shape and colourful leaves, and people likethem much. This research was aimed to study: (i) the diversity of forma in Codiaeum variegatum, and (ii) number of those forma in Yogyakarta. There are thirteen forma in Yogyakarta, namely: C. verieqstum picturn 'Graigi', C. variegatum Golfinger, C. variegatum pictum, C. variegatum pictum Yoseph's coat, C. variegatum Mortii, C. variegatum Gold, C. variegatum Eggs, C. variegatum Tendril, C. variegatum pictum Princess Mary, C. variegatum pictum Princess, C. variegatum pictum Caudatum, C. variegatum Caudatum, and C. variegatum Sulcal. The two forma special form called kidang emas and lancuran planted in cemetery by Javanese due to its ritual value of yellow colour. The other forma its outdoor garden plants. The leaves of forma have degradation on colours and variation on shapes.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey word: puring (Codiaeum variegatum), keragaman, forma, magis